Online student performance evaluation in system-Z mainframe - Noor Zalina, Razali (2012)
Today,the term mainframe can best be used to describe a style of operation,applications and operating system facilities.The z mainframe plays a central role in the daily operations of the world’s largest organizations and the daily lives of most people.Nowadays,mostly the system is manual entry into database and use a single entry at a time. There are also unformatted data stored.Thus,this project paper is done to present a design of online student performance evaluation in system-z mainframe where it gives benefit to create automated data entry into the database via COBOL.Besides that,to create a batch type input and output system and to generate a formatted report stored in an independent flat file as output.Furthermore,this project is build to make the recording more efficient,easy to be stored and retrieved from the database.This project design consists of the workflow of the developed system diagrams,logical use case diagram and the example design interfaces itself.This project also reviewed the current system and the existing system that related to online student performance evaluation.Other than that,this project paper reviewed on the current technique on operating system in mainframe which can support thousands of applications and input or output devices to simultaneously serve thousands of users. Generally this system has met its objectives which are to develop “Online Student Performance Evaluation in System-z Mainframe”to make the new systematically.After making a research, analysis, and lastly make a testing to all programs, finally the “Online Student Performance Evaluation in System-z Mainframe”is successfully developed.